REFUSAL STRATEGY PERFORMED BY INDONESIAN EFL LEARNER - Nenden Sri Rahayu (Indonesian EFL Journal, 2019)
The research investigates the speech act recognition of refusing as made by Indonesian learners of English as a foreign language, native Indonesian, and native English. It involves three groups: 13 Indonesian EFL Learners (IELs), 13 Indonesian Native Speakers (INSs), and 13 American Native Speakers (NSs) of English. They were asked to respond to ten different situations, in which they carry out the speech act of refusal. Their strategies in refusing were compared one another in order to find out whether the refusal performed by Indonesian EFL Learner (IELs) correspond more closely with those of the Indonesian Native Speakers (INSs) or with speakers of the target language, the American Native Speakers (NSs). The data, collected from a Discourse Completion Test (DCT) which was developed by Blum-Kulka, were analyzed and categorized based on Azisâ€™s categories (2000). Results indicated that although a similar range of refusal strategies were available to the two language groups, cross-cultural variation still exists. The data involved some contextual variables, which include the status of interlocutors (higher, equal, or lower status) and eliciting acts, i.e., requests, invitations, offers, and suggestions.Keywords: Indonesian EFL Learners; interlanguage pragmatics; refusal strategy; speechÂ act.